2022
DOI: 10.1186/s12884-022-04774-0
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic genito-urinary fistula following cesarean birth in nine sub-Saharan African countries: a retrospective review

Abstract: Background Genito-urinary fistulas may occur as complications of obstetric surgery. Location and circumstances can indicate iatrogenic origin as opposed to pressure necrosis following prolonged, obstructed labor. Methods This retrospective review focuses on 787 women with iatrogenic genito-urinary fistulas among 2942 women who developed fistulas after cesarean birth between 1994 and 2017. They are a subset of 5469 women who sought obstetric fistula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 24 publications
3
7
0
Order By: Relevance
“…Evidence has been mounting about the proportion of iatrogenic fistula amongst repaired fistulas [ 18 21 ]. In a separate analysis we reported that 26.8% (787/2,942) of women with fistula after cesarean section have injuries caused by surgery rather than pressure necrosis from prolonged, obstructed labor [ 7 ]. This aligns with reports from others [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence has been mounting about the proportion of iatrogenic fistula amongst repaired fistulas [ 18 21 ]. In a separate analysis we reported that 26.8% (787/2,942) of women with fistula after cesarean section have injuries caused by surgery rather than pressure necrosis from prolonged, obstructed labor [ 7 ]. This aligns with reports from others [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite its important place in enabling fistula elimination, however, rising numbers of cesarean births increase the risk of all associated complications, including iatrogenic fistula. Location and circumstances can indicate that a fistula is iatrogenic rather than attributable to pressure necrosis [7,11]. Evidence has been mounting about the proportion of iatrogenic fistula amongst repaired fistulas [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Cape Town, South Africa. 5 Leiden University Medical Centre and Athena Institute VU University, Amsterdam, the Netherlands. 6 Centre of Excellence in Women and Child Health, Aga Khan University, Nairobi, Kenya.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…While most genital fistulas follow childbirth in lowresourced settings, fistulas in well-resourced settings occur primarily as surgical complications [1,2]. A rising proportion of genital fistulas may be attributable to surgical accidents in low-resource settings as well [3][4][5].…”
Section: Introductionmentioning
confidence: 99%